Handbook of job aids - Rossett, Allison (Jossey-Bass Pfeiffer San FranciscoUS, 1991)
Defines job aids; reviews the benefits and drawbacks they present; and suggests appropriate situations for using them. Advises on suitable formatting, and provides detailed steps for developing them. Presents examples and reviews of job aids designed to inform, to support procedures, to coach perspectives, and support decisions. Looks at emerging trends in organizations, and provides examples of the technological future for job aids.